Internationalization of higher education of China as the factor of university competitiveness increase - Petruk, Galina V. (2018)
In the modern world, the internationalization of higher education is a general trend of education and science development covering almost all countries of the world. The PRC is not an exception. Education is one of the most important priorities of China state policy. The Chinese government believes that the preparation of students abroad, especially in high-ranking universities of the world, is the means of education quality provision and improvement. After the performance of higher education reforms, its position has significantly strengthened on the international educational market. For a decade and a half, the number of Chinese students studying at foreign universities increased by 9.5 times, and the number of foreign students studying at Chinese universities increased by 27.3 times. The main tools for the internationalization of higher education in China are the following ones: the improvement of educational service quality, an active policy of Chinese university promotion at the world market, the change of the approach to teacher hiring and promotion, the transition to foreign textbooks, and the opening of joint educational programs.